2011
DOI: 10.5042/jacpr.2011.0017
|View full text |Cite
|
Sign up to set email alerts
|

Mutually violent attitudes: effects on intimate partner violence and mental health symptoms among couples in Botswana, Africa

Abstract: The present study investigated the prevalence of mutual violence, violent attitudes and mental health symptoms among students in Botswana, Africa. The sample consisted of 562 university students from Botswana University in heterosexual relationships. Participants completed self-report surveys that asked about violent attitudes, partner violence, controlling behaviours, and mental health symptoms. Results were that respondent and respondent partner's violent attitudes, partner violence and controlling behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…However, significant effects were more apparent in relation to being victimized by abuse than by perpetrating abuse. This is consistent with previous findings concerning IPV victimization,7,8,17,23,24,26,36,52 as well as IPV perpetration 35,3739,53,54…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, significant effects were more apparent in relation to being victimized by abuse than by perpetrating abuse. This is consistent with previous findings concerning IPV victimization,7,8,17,23,24,26,36,52 as well as IPV perpetration 35,3739,53,54…”
Section: Discussionsupporting
confidence: 93%
“…However, not much research attention has been given to the relation between women’s IPV perpetration and their own health status. Existing studies, which are mainly from Western countries, have revealed that female perpetrators of IPV can have mental health problems, such as depression and anxiety 18,24,26,3538. As far as we know, only one study has addressed the comparative effects of women’s use of various IPV types on their own mental health, with results showing that psychological aggression was more strongly associated with depression, anxiety, and somatization than with other IPV types, eg, physical assault 18…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher levels of difficulties were found in victims of violence compared to perpetrators of violence. The results were consistent with previous research results related to the victims (Jankey, Próspero, & Fawson, 2011) as well as the perpetrators of partner violence (Henning, Renauer & Holdford, 2006).…”
Section: Disscusionsupporting
confidence: 93%
“…Consistent with this study only few foreign studies showed that men were more likely than women to physically aggress towards their partners. For example, in support of this study, with ethnically diverse sample of university students Prospero (2009) found that males were much more likely to perpetrate physical violence towards their partners than females [24].…”
Section: Discussionmentioning
confidence: 66%
“…A lot of studies supported the conclusion that women are as aggressive as their counterpart men in intimate relationships [19][20][21][22][23]. With ethnically diverse sample of university students, Prospero (2009) also found that males were much more likely to perpetrate physical violence towards their partners than females [24].…”
Section: Introductionmentioning
confidence: 99%